Predictive factors for complications in children with esophageal atresia and tracheoesophageal fistula. Issue 3 (1st April 2015) - Shah, R.; Varjavandi, V.; Krishnan, U.
Summary: The objective of this study was to describe the incidence of complications in children with esophageal atresia (EA) with or without tracheoesophageal fistula (TEF) at a tertiary pediatric hospital and to identify predictive factors for their occurrence. A retrospective chart review of 110 patients born in or transferred to Sydney Children's Hospital with EA/TEF between January 1999 and December 2010 was done. Univariate and multivariate regression analyses were performed to identify predictive factors for the occurrence of complications in these children. From univariate analysis, early esophageal stricture formation was more likely in children with 'long-gap' EA (odds ratio [OR] = 16.32). Patients with early strictures were more likely to develop chest infections (OR = 3.33). Patients with severe tracheomalacia were more likely to experience 'cyanotic/dying' (OR = 180) and undergo aortopexy (OR = 549). Patients who had gastroesophageal reflux disease were significantly more likely to require fundoplication (OR = 10.83) and undergo aortopexy (OR = 6.417). From multivariate analysis, 'long-gap' EA was a significant predictive factor for late esophageal stricture formation ( P = 0.007) and for gastrostomy insertion ( P = 0.001). Reflux was a significant predictive factor for requiring fundoplication ( P = 0.007) and gastrostomy ( P = 0.002). Gastrostomy insertion ( P = 0.000) was a significant predictive factor for undergoing fundoplication. Having a prior fundoplication ( P = 0.001) was a significant predictive factor for undergoing a subsequent aortopexy. Predictive factors for the occurrence of complications post EA/TEF repair were identified in this large single centre pediatric study.